RANCANG BANGUN SISTEM INFORMASI SCHEDULE MANAGEMENT BERBASIS WEB - Trissa Amelia Sarjito; Marhaeni Marhaeni (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2021)
The development of technology is growing rapidly, it is happening in Indonesia. Even the role of technology is considered really capable of replacing humans on some activities. However, the growth of technology itself is not always accompanied by the use of technology. The lack of knowledge of its application is the main reason the problem occurs. The same thing happened in APTIKA field in Diskominfo Depok City At the research site, the lack of technology utilization in terms of management schedule process. Where APTIKA staff have to do scheduling manually by writing the meeting schedule on the board while staff who have a lot of work sometimes forget to write the agenda. This becomes a problem so that the writing of the schedule becomes difficult for APTIKA staff, knowing that the scheduling condition is not carried out properly and the lack of optimal activities. The system to be created is designed to help APTIKA staff schedule web-based meeting agendas. While the research methodology used in this research is an object-oriented method. And the system development method used is waterfall method. Keywords : Information Systems, Scheduling, Waterfall Methods.